Fast ISP coding mode optimization algorithm based on CU texture complexity for VVC - Liu, Zhi; Dong, Mengjun; Guan, Xiao Han; Zhang, Mengmeng; Wang, Ruoyu (EURASIP journal on image and video processing, 2021)
In lately published video coding standard Versatile Video Coding (VVC/ H.266), the intra sub-partitions (ISP) coding mode is proposed. It is efficient for frames with rich texture, but less efficient for frames that are very flat or constant. In this paper, by comparing and analyzing the rate distortion cost (RD-cost) of coding unit (CU) with different texture features for using and not using ISP(No-ISP) coding mode, it is observed that CUs with simple texture can skip ISP coding mode. Based on this observation, a fast ISP coding mode optimization algorithm based on CU texture complexity is proposed, which aims to determine whether a CU needs to use ISP coding mode in advance by calculating CU texture complexity, so as to reduce the computation complexity of ISP. The experimental results show that under All Intra (AI) configuration, the coding time can be reduced by 7%, while the BD rate only increase by 0.09%.